Boosted food web productivity through ocean acidification collapses under warming. (27th April 2017) - Goldenberg, Silvan U.; Nagelkerken, Ivan; Ferreira, Camilo M.; Ullah, Hadayet; Connell, Sean D.
Abstract: Future climate is forecast to drive bottom‐up (resource driven) and top‐down (consumer driven) change to food web dynamics and community structure. Yet, our predictive understanding of these changes is hampered by an over‐reliance on simplified laboratory systems centred on single trophic levels. Using a large mesocosm experiment, we reveal how future ocean acidification and warming modify trophic linkages across a three‐level food web: that is, primary (algae), secondary (herbivorous invertebrates) and tertiary (predatory fish) producers. Both elevated CO2 and elevated temperature boosted primary production. Under elevated CO2, the enhanced bottom‐up forcing propagated through all trophic levels. Elevated temperature, however, negated the benefits of elevated CO2 by stalling secondary production. This imbalance caused secondary producer populations to decline as elevated temperature drove predators to consume their prey more rapidly in the face of higher metabolic demand. Our findings demonstrate how anthropogenic CO2 can function as a resource that boosts productivity throughout food webs, and how warming can reverse this effect by acting as a stressor to trophic interactions. Understanding the shifting balance between the propagation of resource enrichment and its consumption across trophic levels provides a predictive understanding of future dynamics of stability and collapse in food webs and fisheries production. Abstract : Using a large mesocosm experiment, we reveal how future ocean acidification and warming modify trophic linkages across a 3‐level food web: that is, primary (algae), secondary (herbivorous invertebrates) and tertiary (predatory fish) producers. Our findings show how anthropogenic CO2 can function as a resource that boosts productivity throughout food webs and how warming can reverse this effect by acting as a stressor to trophic interactions. We provide a mechanistic understanding of the shifting balance between the propagation of resource enrichment and its consumption across trophic levels, which is a key for predicting future dynamics of stability and collapse in food webs and fisheries production.